Etika Di Sekitar Perawatan Lansia - Rudy Hartanto (Respons: Jurnal Etika Sosial, 2008)
Abstract: This article talks about ethical problem in medicine, mainly about the old people with alzhimer. Being old is not anyone choise, because it is a natural proccess of every living beings. Many people get alzhimer by the time they get older. The ethical question according to that matter, is it ethical for the doctor to revealed his diognose to the alzhimer patient. Since revealed the analized would make patiens become restless. All the problem discuss in this article.Kata Kunci: Persoalan orang lanjut usia, Tua kronologis dan biologis, Alzhimer